Beneficial Effects of Rosmarinic Acid on IPEC-J2 Cells Exposed to the Combination of Deoxynivalenol and T-2 Toxin - Judit Mercédesz Pomothy; Réka Fanni Barna; Erzsébet Anna Pászti; Ákos Babiczky; Áron Szóládi; Ákos Jerzsele; Erzsébet Pásztiné Gere (Hindawi Limited, 2020)
Mycotoxin contamination in feedstuffs is a worldwide problem that causes serious health issues both in humans and animals, and it contributes to serious economic losses. Deoxynivalenol (DON) and T-2 toxin (T-2) are major trichothecene mycotoxins and are known to challenge mainly intestinal barrier functions. Polyphenolic rosmarinic acid (RA) appeared to have antioxidant and anti-inflammatory properties in vitro. The aim of this study was to investigate protective effects of RA against DON and T-2 or combined mycotoxin-induced intestinal damage in nontumorigenic porcine cell line, IPEC-J2. It was ascertained that simultaneous treatment of DON and T-2 (DT2: 1 μmol/L DON+5 nmol/L T−2) for 48 h and 72 h reduced transepithelial electrical resistance of cell monolayer, which was restored by 50 μmol/L RA application. It was also found that DT2 for 48 h and 72 h could induce oxidative stress and elevate interleukin-6 (IL-6) and interleukin-8 (IL-8) levels significantly, which were alleviated by the administration of RA. DT2 administration contributed to the redistribution of claudin-1; however, occludin membranous localization was not altered by combined mycotoxin treatment. In conclusion, beneficial effect of RA was exerted on DT2-deteriorated cell monolayer integrity and on the perturbated redox status of IPEC-J2 cells.